2017
DOI: 10.1016/j.jaut.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CXCR3 deficiency exacerbates murine autoimmune cholangitis by promoting pathogenic CD8+ T cell activation

Abstract: CXC Chemokine Receptor 3 (CXCR3) is functionally pleiotropic and not only plays an important role in chemotaxis, but also participates in T cell differentiation and may play a critical role in inducing and maintaining immune tolerance. These observations are particularly critical for autoimmune cholangitis in which CXCR3 positive T cells are found around the portal areas of both humans and mouse models of primary biliary cholangitis (PBC). Herein, we investigated the role of CXCR3 in the pathogenesis of autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Deletion of CXCR3 from the CD25 −/− mice resulted in aggravated hepatic inflammatory responses with increased CD8 + T cells associated with their increased production of inflammatory cytokine IFN-γ in the liver, but alleviated colitis with decreased CD4 + T cells associated with their reduced production of IL-17A in the colon. These results are in agreement with our previous findings on the different roles of IFN-γ and IL-17A in regulating the severity of cholangitis versus colitis ( 10 , 20 ). Together these findings indicate that the effects of CXCR3 on the autoimmune diseases were organ specific.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Deletion of CXCR3 from the CD25 −/− mice resulted in aggravated hepatic inflammatory responses with increased CD8 + T cells associated with their increased production of inflammatory cytokine IFN-γ in the liver, but alleviated colitis with decreased CD4 + T cells associated with their reduced production of IL-17A in the colon. These results are in agreement with our previous findings on the different roles of IFN-γ and IL-17A in regulating the severity of cholangitis versus colitis ( 10 , 20 ). Together these findings indicate that the effects of CXCR3 on the autoimmune diseases were organ specific.…”
Section: Discussionsupporting
confidence: 94%
“…Mononuclear cells from liver, spleen, and MLN were isolated and stained as described ( 10 ). Colon LPL were isolated using a standardized protocol ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of B cell in the immunopathology of autoimmune cholangitis is well documented in patients with PBC and animal models ( 6 , 9 , 10 , 13 , 15 , 52 55 ). This study demonstrated that B cells promote the development of PBC-like liver disease, and partial but substantial B-cell depletion with humanized anti-hCD20 antibody (TKM-011) effectively attenuates bile duct damage in the hCD20 hFcγR-expressing dnTGF-βRII mice.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of dominant negative TGF-β receptor II (dnTGF-βRII) mice as a model for human PBC ( 12 ). The expression of dnTGF-βRII is limited to selected cell lineages including CD4 + , CD8 + , and CD1d-restricted natural killer T (NKT) cells; B cell function is normal in this model ( 12 , 13 ). We previously demonstrated that treatment of juvenile mice with a monoclonal anti-mouse CD20 antibody was effective in preventing PBC, but that responses were reduced when treatment was initiated in older mice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%